AN ISLAMIC PERSPECTIVE ON THE FILM “ASSALAMU’ALAIKUM BEIJING ”: A STUDY IN ENGLISH LITERATURE - Hidayat, Tawvicky; Mujibno, Mujibno; Anam, Saiful (Reflektika, 2025)
This study aims to explore the film "Assalamualaikum Beijing" from an Islamic perspective using a literature review approach. The film, adapted from a novel by Asma Nadia, is directed by Guntur Soeharjanto and tells the story of a love affair between two people. The main focus of this study is to uncover the representation of Islamic teachings, including aspects of faith, morality, Islamic brotherhood, and the spirit of seeking knowledge. The method used is content analysis, examining Islamic themes reflected in the storyline, dialogue between characters, and character portrayals. The analysis shows that the film consistently displays Islamic values, particularly in promoting the importance of education, spiritual development, and social relations. Furthermore, the film successfully conveys a universal Islamic message that remains relevant in the context of contemporary life. This research is expected to enrich the study of Islam in popular media and serve as a reference for similar research in the future.